Climate Change in Indonesia's Coastal Regions: A Review - I Dewa Putu Oka Diatmika; Dewi Sartika (Journal of Epidemiology and Health Science, 2025)
Background: Climate change, primarily driven by global warming, has substantial negative impacts on coastal areas, particularly affecting the livelihoods of fishing communities. Rising temperatures, changing weather patterns, and sea-level rise have made fishing activities increasingly challenging. These environmental changes lead to reduced fish stocks, declining income from fishing, and broader socio-economic disruptions for coastal populations. Furthermore, the health of fishing communities is at risk due to the scarcity of clean water and decreased nutritional intake resulting from reduced fish catches. Objective: This study aims to systematically review the scientific literature on the impacts of climate change on fishing communities and coastal areas, with particular emphasis on the socio-economic and health consequences, as well as adaptation strategies. Methods: A Systematic Literature Review (SLR) was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant scientific articles published between 2010 and 2024 were collected and analyzed. The inclusion criteria focused on studies addressing climate change, its impacts on coastal communities, and adaptation efforts by fishers. Results: The review findings indicate that climate change has far-reaching negative impacts on the livelihoods of coastal fishing communities. From a health perspective, climate change exacerbates the risk of disease transmission due to limited access to clean water and contributes to malnutrition resulting from reduced fish availability. Economically, decreased fish catches directly reduce fishermen's incomes, increasing their vulnerability. The findings also highlight the importance of adaptive capacity in maintaining the resilience of fishing communities, ensuring their economic activities and health status are not severely compromised. Conclusion: Climate change poses serious threats to the health, economic stability, and social well-being of fishing communities. Enhancing the adaptability of fishermen is crucial to mitigate these impacts. In addition, policymakers must develop comprehensive, multi-sectoral adaptation strategies that address the entire chain of vulnerability—from environmental changes to economic and health outcomes. Such policies should be implemented holistically, from upstream planning to downstream execution, to ensure they effectively support the resilience of affected coastal populations. Keywords: Climate Change, Global Warming, Socioeconomic Factors, Coastal Communities, Indonesia